2020
DOI: 10.13057/biodiv/d211235
|View full text |Cite
|
Sign up to set email alerts
|

Yield performance of several peanut cultivars grown in dryland with semi-arid climate in Sumba Timur, Indonesia

Abstract: Abstract. Rahmianna A, Wijanarko A, Purnomo J, Baliadi Y. 2020. Yield performance of several peanut cultivars grown in dryland with semi-arid climate in Sumba Timur, Indonesia. Biodiversitas 21: 5747-5757.  Peanut (Arachis hypogaea L.) is the fourth major food crops in Indonesia after rice, maize, and soybean. The seeds contain oil, protein, and carbohydrate which are beneficial to human health. Despite its health benefit, farmers sell all pods for cash. The dryland areas with semi-arid climates, where there i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Number of mature pods per plant ranged from 13-25 pods with average 17 pods. These high numbers of mature pods really support high pod yield per plant as [9][10] reported that pod yield per plant positively correlated with number of mature pods per plant and seed yield per plant. It can be informed that in the current study, there were four genotypes (GH 3, GH 6, GH 10, and GH 11) with small seed, and the other eight genotypes had medium seed size.…”
Section: Resultsmentioning
confidence: 68%
“…Number of mature pods per plant ranged from 13-25 pods with average 17 pods. These high numbers of mature pods really support high pod yield per plant as [9][10] reported that pod yield per plant positively correlated with number of mature pods per plant and seed yield per plant. It can be informed that in the current study, there were four genotypes (GH 3, GH 6, GH 10, and GH 11) with small seed, and the other eight genotypes had medium seed size.…”
Section: Resultsmentioning
confidence: 68%
“…In addition, peanut by-products such as stems and nodules from roots are rich in nitrogen nutrients, allowing more microorganisms to survive in sandy soil and reducing the amount of chemical fertilizer necessary for the next rice crop [29]. Whereas HYV rice typically requires more nitrogen fertilizer and pesticide use than peanuts [30].…”
Section: B Drought Tolerance and Improved Soil Environment Of Peanut ...mentioning
confidence: 99%
“…is..one.of.the largest legume crops worldwide, containing carbohydrates, minerals, and vitamins. Compared to other nuts, peanut is richer in protein material [6,13]. Peanuts are consumed worldwide and have become part of various snacks and recipes in different countries.…”
Section: Introductionmentioning
confidence: 99%